BS EN 60332-3-10 AMD AA. Tests on electric and optical fibre cables under fire conditions. Part 3-10. Test for vertical flame spread of vertically-mounted bunched wires or cables. Apparatus (15th May 2020) - British Standards Institution,
No abstract available